2016
DOI: 10.3122/jabfm.2016.02.150356
|View full text |Cite
|
Sign up to set email alerts
|

Access to Primary Care in US Counties Is Associated with Lower Obesity Rates

Abstract: Background: Obesity causes substantial morbidity and mortality in the United States. Evidence shows that primary care physician (PCP) supply correlates positively with improved health, but its association with obesity in the United States as not been adequately characterized. Our purpose was to characterize the association between PCP supply in US counties and adult obesity.Methods: We performed a multivariate logistic regression analysis to examine the relationship between county-level PCP supply and individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Yet with our findings, primary care clinicians, overwhelmed by the burdens of treating patients with severe obesity, can be encouraged that simply offering greater contact to patients with severe obesity improves weight loss. In addition, our findings lend support to the call for improved primary care access, and thus more office visits, for patients with severe obesity as they have shown to be at risk for inferior primary care access and preventive care [10,11]. The next reasonable study would tease out how and why patients with severe obesity lose more weight when they have more visits with their primary care clinicians.…”
Section: Discussionsupporting
confidence: 65%
“…Yet with our findings, primary care clinicians, overwhelmed by the burdens of treating patients with severe obesity, can be encouraged that simply offering greater contact to patients with severe obesity improves weight loss. In addition, our findings lend support to the call for improved primary care access, and thus more office visits, for patients with severe obesity as they have shown to be at risk for inferior primary care access and preventive care [10,11]. The next reasonable study would tease out how and why patients with severe obesity lose more weight when they have more visits with their primary care clinicians.…”
Section: Discussionsupporting
confidence: 65%
“…Regarding the inverse correlation of major CVD prevalence with the number of cardiologists, previous studies have reported possible explanations. They have described that higher physician density could improve specific health outcomes ( 7 , 8 ). With a higher density, each physician likely has to care for fewer patients, the patients have more alternatives and they have to travel shorter distances.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study similarly found a negative association between pediatrician density and mortality of under 5-year-olds ( 6 ). Several other studies have noted that greater primary care physician supply is associated with improvements in health outcomes such as obesity rates ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with Siddiqi et al we find that there are cross-national differences in the prevalence of morbid obesity, in the shape of the socioeconomic distribution and the absolute and relative magnitude of inequalities ( Siddiqi et al, 2015 ). Inequalities in income and education may influence health via multiple downstream mediators including, but not restricted to, lifestyle choices, diet quality and access to resources for physical activity ( Benach & Muntaner, 2007 ; Devaux, 2013 ; Devaux & Sassi, 2013 ; Gaglioti, Petterson, Bazemore & Phillips, 2016 ). Educational attainment is generally expected to be associated with higher income but this effect may be modified by other characteristics including age-group, ethnicity and gender ( Braveman, Cubbin & Egerter, 2005 ).…”
Section: Discussionmentioning
confidence: 99%